PARKINSON'S FAMILIES PROJECT: RECRUITMENT OF FAMILIAL PD PATIENTS VIA THE BNSU. Issue 12 (15th November 2016) - Hong, James; Tan, Manuela; Rizig, Mie; Brugaletta, Concetta; Cable, Sarah; Lubbe, Steven; Morris, Huw
Abstract : The Parkinson's Families Project is a multi-centre genetic epidemiology study. Aims: To identify new genetic variants that predispose to or cause familial or early onset PD. Methods: Families with either familial or early onset PD are recruited. The ABN BNSU is a source of participant recruitment, by which patients with familial PD from across the UK can be notified to the study team monthly by ABN members. Permission to contact the patient is obtained from the patient through the consultant. Following informed consent, patients provide blood samples for genetic analysis and complete standard study questionnaires. Results: (April 2015–Jan 2016): Over 10 months we have received 96 BNSU referrals (mean 10/month) from 33 consultants. We have received 35 permission-to-contact forms from patients (36.5%) and 19 patients/families have completed study enrollment (19.8% recruitment rate). Conclusions: The BNSU is an invaluable source of referral for patients with rare diseases from across the UK, and we currently have a 20% patient recruitment rate. However, there is a delay from study initiation to completion of patient recruitment. We could improve the relatively low rate of patient contact by establishing a formal system of regular follow-ups for consultants and an anonymised tracking system for BNSU-referred patients. Finally, we suggest the possibility of multi-source recruitment through Parkinson's UK, local study sites, geriatricians and PD nurses.